Pengembangan Lembar Kerja Siswa Berbasis Pendekatan Pemecahan Masalah Dalam Pembelajaran Ekonomi Di MA Hasanah Pekanbaru - Badriyah, Miftahul Shulha (EL-EMIR Institute, 2024)
This study aims to develop Student Worksheets (LKS) based on a problem-solving approach in Economics subjects at Madrasah Aliyah (MA) Hasanah Pekanbaru. The main objective of developing this LKS is to improve students' critical and creative thinking skills in understanding economic concepts through a systematic problem-solving approach. The research method used is the research and development method (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study involved several stages, starting from analyzing student needs and curriculum, designing LKS, to testing the product in class. The subjects of the study were grade XI students of MA Hasanah Pekanbaru who were selected randomly. Data collection was carried out through observation, interviews, questionnaires, and learning outcome tests. The data obtained were analyzed using quantitative descriptive techniques to determine the increase in student learning outcomes before and after the use of LKS based on problem solving. The results showed that the LKS developed was able to improve students' understanding of economic concepts and encourage critical thinking skills and problem solving. Significant improvement can be seen from the pre-test and post-test results, where the average student score increased by 25%. In addition, the student response to this LKS was very positive, where most students felt more challenged and motivated in the learning process. Based on the results of this study, LKS based on a problem-solving approach can be used as an alternative in improving the quality of economic learning at MA Hasanah Pekanbaru.